2021
DOI: 10.3390/antibiotics10121477
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Remdesivir over Two Waves of the SARS-CoV-2 Pandemic

Abstract: The aim of this study is to describe the features, the outcomes, and the clinical issues related to Remdesivir administration of a cohort of 220 patients (pts) with COVID-19 hospitalized throughout the last two pandemic waves in Italy. One hundred and nine pts were enrolled from 1 September 2020, to 28 February 2021 (Group A) and 111 from 1 March to 30 September 2021 (Group B). Notably, no differences were reported between the two groups neither in the timing of hospitalization. nor in the timing of Remdesivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…Some reports have shown little or no impact from this treatment, either alone or in association with steroids, on clinically relevant outcomes such as intensive care unit (ICU) admission or mortality [ 7 , 8 , 9 , 10 ]. Conversely, other studies suggested that it could be useful, as an add-on treatment, in adults with persistent fever and dyspnea and moderate lung involvement on chest CT, reducing ICU admission, length of hospital stay, and even mortality [ 11 , 12 , 13 , 14 , 15 ], especially when administered in the first 5 days of symptoms [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown little or no impact from this treatment, either alone or in association with steroids, on clinically relevant outcomes such as intensive care unit (ICU) admission or mortality [ 7 , 8 , 9 , 10 ]. Conversely, other studies suggested that it could be useful, as an add-on treatment, in adults with persistent fever and dyspnea and moderate lung involvement on chest CT, reducing ICU admission, length of hospital stay, and even mortality [ 11 , 12 , 13 , 14 , 15 ], especially when administered in the first 5 days of symptoms [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, they observed a reduction in heart rate, but there was no cardiovascular system (CVS) toxicity even with severe CVS comorbidity. 20 A recent review article also found a similar safety profile. Multiple‐dose of remdesivir resulted in reversible hepatocellular enzyme elevations, but there was no renal or hepatic toxicity.…”
Section: Remdesivirmentioning
confidence: 75%
“…According to a group of scientists focusing on renal, cardiac, and hepatic safety, they found remdesivir causing no significant changes in glomerular filtration rate and liver enzymes even in impaired patients. However, they observed a reduction in heart rate, but there was no cardiovascular system (CVS) toxicity even with severe CVS comorbidity 20 . A recent review article also found a similar safety profile.…”
Section: Remdesivirmentioning
confidence: 83%
See 1 more Smart Citation
“…For patients with SARS-CoV-2 pneumonia, Poliseno and the other researchers on the Foggia team present a very relevant case history on the use of remdesivir and its efficacy and safety profile [ 7 ]. Their data show a low rate of ICU admission, a high rate of clinical recovery and good drug safety observed in COVID-19 patients treated with remdesivir during two distinct pandemic waves.…”
mentioning
confidence: 99%